Hubungan Penguasaan Konsep dengan Kemampuan Menilai Kredibilitas Sumber Informasi Menggunakan Problem Based Learning (PBL) pada Materi Pencemaran Lingkungan - Warsita, Adnes Ningrum; Kusumastuti, Mimin Nurjhani; Shintawati, Rita (Department of Biology Education, Universitas Pendidikan Indonesia, 2018)
The aim of this research was to reveal a relationship between students' concepts mastery on the matter of environmental pollution with the ability to assess the credibility of the source through problem-based learning. The type of research is pre-experiment which analyzed by correlation method. Then the study design using the post-test only design with a total sample of 39 students of grade 10 and for sampling technique uses simple-random sampling technique. Student’s concepts mastery on material environmental pollution are identified using the instrument in the form of multiple choice questions and essay question, while the level of ability to assess the credibility of the source is identified based on the accuracy of the students sort the level of credibility of source and the students' answers on the criteria that they use to sort the credibility of the source, which is scored with a rubric that has been made. The average score of students' mastery of concepts is 74.1 and quite good. In addition, through one sample t-test was also proven when problem-based learning have a real or significant influence on students' mastery of concepts in the matter of environmental pollution. Correlation test is then performed using the non parametric statistical using Spearman correlation, and got score 0.82 for correlation coefficient, which means having a high correlation with a contribution of 67.5%. Thus the conclusions that can be drawn is that there is a high correlation between students' concepts mastery on the matter of environmental pollution with the ability to assess the credibility of the source through problem-based learning.